The Supply Chain System of Cassava on The Tapioca Industry - . Hardoyo; Ahmad Safrudin; Ahmad Komara (Bandar Lampung University (UBL), 2013)
The quantity, quality and continueity guarantee of raw material supply is a one of define factor for the succesfull of production process. To solve the problems of raw material supply on tapioca industry, it is important to develop a correct raw material supply management. That management must be accurate on quantity, quality, continuity and price. One of the developed management is supply chain managementThe purpose of this paper is to make a cassava raw material supply chain on 100 ton product/day on tapioca industry in an affort to manage a continues and stable of raw material supply. The methods use in this research are to assessment of relatedness between tapioca industry raw material supply chain management with related elements and make conceptual design, pre design and detailed design of tapioca industry raw material supply chain.The result show that depending elements to make a tapioca industry supply chain design system are the information of raw material stock both from cassava farmer or suppliers, the supply information from the patner and buffer stock , the price of raw material, tranportation. Buffer and partnership pattern are two kinds of the best methods to guarantee the fulfill requirement of tapioca industry raw material. Raw material tranportation, storehouse and refraction are important components on the supply chain management.Based on 100 ton tapioca/day production capacity, convertion of raw material ( cassava) to tapioca product is 5 :1, operation time is 250 days/year, it is need 125.000 ton/year raw material ( cassava ). The requirement suplly of raw material are obtained from cassava farmer 15.000 ton, partner 30.000 ton, buffer 40.000 ton and agent 40.000 ton.